Hypoxia may be a determinative factor in COVID-19 progression - Grieb, Pawel (Curr Res Pharmacol Drug Discov, 2021)
The disease which develops following SARS-CoV-2 virus infection, known as COVID-19, in most affected countries displays mortality from 1.5% to 9.8%. When leukocytosis due to granulocytosis, thrombocytopenia, and increased level of D-dimers are detected early during the disease course, they are accurate predictors of mortality. Based on the published observations that each of the aforementioned disturbances by itself may appear as a consequence of hypoxia, a hypothesis is presented that early hypoxia consequential to sleep apnea and/or blunted respiratory response to chemical stimuli is an early determinant of COVID-19 progression to the severe and critical stage. Further, it is noted that host-directed therapies which may counteract hypoxia and its early downstream effects are initiated only upon hospitalization of COVID-19 patients, which is too late to be fully effective. An example is anticoagulation treatment with low molecular weight heparin. Repurposing drugs which could counteract some early posthypoxic events, such as fluvoxamine, amantadine and N-acetylcysteine, for post-exposure prophylaxis of SARS-CoV-2 infection and early prehospital treatment of COVID-19, is indicated.